DELVING INTO THE COMPLEXITY OF ISLAMIC THOUGHT ABOUT SPIRIT: THE NATURE OF THE SPIRIT IN THE LIGHT OF NURUDDIN AL-RANIRI - Arifka, Angga (Institut Agama Islam Ngawi, 2025)
This article examines al-Raniri’s views on spirit. In Islamic thought, spirit is an important matter discussed by Muslim theologians, Muslim philosophers and Sufis. They argue with each other about the nature of spirit. Using content analysis, this library research attempts to portray how al-Raniri navigates the complexity of the Islamic thought regarding spirit. This study found that al-Raniri seeks to synthesize various views. Nonetheless, he was more inclined towards the views of the Sufis than the theologians and philosophers. Al-Raniri views the spirit as a subtle substance that is located in the heart and will last forever even if the body is destroyed. Keywords: Al-Raniri, Islamic thought, the human spirit, the nature of the spirit.